2021
DOI: 10.1016/j.ijcha.2021.100747
|View full text |Cite
|
Sign up to set email alerts
|

Coronary lipid-rich plaque characteristics in Japanese patients with acute coronary syndrome and stable angina: A near infrared spectroscopy and intravascular ultrasound study

Abstract: Highlights This study aimed to evaluate the characteristics of lipid-rich plaque (LRP) in Japanese. The maxLCBI 4mm significantly predicted acute coronary syndrome culprit lesion. Almost 20% of patients had at least one high-risk LRP in non-culprit lesion segment in same vessel. No surrogate maker (lipids and inflammation) for a high-risk LRP was found. Direct intravascular evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…LP-PLA2 is a key indicator in the study of clinical vascular disease and an independent risk factor for cardiovascular disease mostly used to study inflammatory response mediators [2]. e pathological basis of ACS in the elderly is the rupture of coronary atherosclerotic plaque, followed by complete or incomplete occlusive thrombosis [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LP-PLA2 is a key indicator in the study of clinical vascular disease and an independent risk factor for cardiovascular disease mostly used to study inflammatory response mediators [2]. e pathological basis of ACS in the elderly is the rupture of coronary atherosclerotic plaque, followed by complete or incomplete occlusive thrombosis [3].…”
Section: Discussionmentioning
confidence: 99%
“…Acute coronary syndrome (ACS) refers to a series of acute symptoms caused by changes in the position of plaques in the coronary arteries that a ect the ow of blood in the arteries. Such symptoms can cause acute myocardial ischemia, myocardial infarction, angina, and thrombus [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…We imaged five cylindrical phantom models made from an acrylic resin with known lumen diameters (1.51, 2.03, 3.04, 4.04, and 5.04 mm, respectively) using OFDI (catheter: FastView and console: LUNAWAVE, Terumo Corporation), FD-OCT (Dragonfly JP and ILUMIEN OPTIS, Abbott Vascular), and 6 mechanically rotating IVUS systems including the system 1) 40-MHz IVUS (ViewIT and VISICUBE, Terumo Corporation), 2) 40-MHz IVUS (OptiCross and iLab, Boston Scientific Corporation), 3) 45-MHz IVUS (Refinity and CORE Mobile, Philips Volcano), 4) 60-MHz IVUS (AltaView and VISICUBE, Terumo Corporation), 5) 60-MHz IVUS (OptiCross HD and iLab, Boston Scientific Corporation), and 6) broad-band frequency IVUS (DualPro and MAKOTO, Nipro) [3] , [4] , [5] , [6] , [7] , [8] . Each of the IVUS systems consist of a flexible monorail catheter with a mechanical rotational (1800 rpm) single transducer probe (annular array) at its tip that emits ultrasound waves in the 40–60 MHz range or broad band of frequencies and an electronics console to reconstruct the image [8] .…”
Section: Methodsmentioning
confidence: 99%
“…The presence of increased CRP and high-risk features in OCT of patients hospitalized for an ACS may be an important prognostic clue for subsequent events [ 25 ]. However, other studies have found no association of CRP with lipid-rich plaques or with TCFAs [ 26 , 27 ], with the study of Koga et al additionally pointing towards the association of pentraxin-3, another marker indicative of inflammation, with TCFAs instead of CRP [ 27 ]. A recent study further confirmed this hypothesis, with post-PCI pentraxin-3 being inversely correlated with fibrous cap thickness and positively correlated with lipid core length [ 28 ].…”
Section: Non-invasive Assessment Of the Vulnerable Coronary Atheroscl...mentioning
confidence: 99%